Conserving and prioritizing indigenous fruits in the Philippines - Oraye, C.D.; Chavez, H.D. de; Aguilar, C.H.M.; Makiling, F.C.; Ladia, V.A. Jr.; Enicola, E.E.; Guevara, M.L.D.; Gueco, L.S.; Maghirang, R.G.; Anunciado, M.S.; Monville-Oro, Emilita; Gonsalves, Julian Francis; et al. (2023)
Nutrition-related problems are a widespread challenge in the Philippines. Many factors contribute to these problems - the availability and affordability of fruits, for example, which are jeopardized by challenges such as seasonality and inconsistent yields due to the impacts of climate change. Crop improvement and on-farm diversification, particularly using indigenous fruits (IFs), can help address these challenges, while also improving rural livelihoods, nutrition, food security; and even safeguarding local culture and tradition.